The possible worlds and the neofantastic in Wes Anderson's filmography - Gudziunaite, Laura (Tropelías: Review of Literary Theory and Comparative Literature, 2021)
In the present paper it is tried to offer an analysis of Wes Anderson's filmography from the study of his structure. For it, there are collected the main ideas of the theory of the possible worlds by Doležel and the respective ones of the genre of the fantastic, with its variations in the contemporary age, emphasizing the Latin American magical realism and the neofantastic by Alazraki. In this way, his films are studied by applying the exposed theories. Likewise, the fictional worlds of Anderson are examined, from its narrative structure and the creation of them, and it is observed to what extent can his filmography belong to the fantastic genre and its modern variations.
Keywords: Wes Anderson; Possible worlds; Fictional worlds; The fantastic; The neofantastic